Effect of substrate type on the field performance and chemical composition of highbush blueberry cv.Patriot - Ochmian, Ireneusz; Grajkowski, Józef; Skupieñ, Katarzyna (MTT Agrifood Research Finland, 2010)
The aim of a 3-year study was to compare the effect of substrate type (peat, sawdust and cocoa husk) on the yield, fruit quality, general and phenolic composition, and antioxidant activity of highbush blueberry (Vaccinium corymbosum L.) cultivar Patriot. The largest berries and the highest yield were obtained from bushes grown in sawdust (3.661 kg ha-1). Berries from bushes grown in cocoa husk had the highest content of N (14.25 g kg-1), P (1.17 g kg-1), K (6.51 g kg-1), and Zn (8.78 mg kg-1), as well as P (1.26 g kg-1) and K (6.99 g kg-1) in the leaves. Both the leaves and fruits of plants grown in sawdust had higher Cu concentrations (3.89 and 3.01 mg kg-1). Berries from sawdust-grown bushes had the highest soluble solids (13.1%) and total sugar (10.80 g 100 g-1) content. The fruits obtained from peat-grown bushes exhibited enhanced antioxidant capacity (38.6 ìmol Trolox g-1). However, the highest levels of phenolics were noted in berries produced in the cocoa husk (208.29 mg 100 g-1) and peat-bed system (174.07 mg 100 g-1). Regardless of the type of substrate used, the following phenols were identified (in descending order): anthocyanins>chlorogenic acid>flavonols. Delphinidin-glycosides were the most abundant pigments, and cyanidin, peonidin, petunidin, and malvidin-glycosides were also detected. Total flavonol content (quercetin derivatives and kaempferol 3-rutinoside) was not significantly affected by the type of substrate.
Keywords: Ka; Ta; Vaccinium corymbosum; yield; firmness; macro- and microelements; phenolics